Disciplina en el proceso enseñanza aprendizaje de los estudiantes de primer año de bachillerato paralelos, D. E. F. Sección matutia del Colegio Nacional en Ciencias Juan Montalvo de la ciudad de Machala provincia de El Oro. 2012-2013. - Cabanilla Alfonso, Marjorie Priscila (2013)
This research is of great importance because it is one of the phenomena most frequently mentioned in the educational institutions. For most students and teachers the main cause of discrepancy is discipline an integral part of school work.